2001
DOI: 10.1046/j.1439-037x.2001.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Relations, Abscisic Acid and Yield of Wheat Plants in Relation to the Interactive Effect of Seawater and Growth Bioregulators

Abstract: Irrigation of wheat plants with seawater (10 and 25 %) led to significant increases in free and bound abscisic acid (ABA) in leaves, especially at 25 %. The relative water content (RWC) and water use efficiency (calculated from grain yield, WUEG, or from biomass yield, WUEB) of the seawater‐irrigated plants were lower than those of the control. Grain pre‐soaking in gibberellic acid (GA3), indole‐3‐acetic acid (IAA) or ABA reduced the levels of accumulated ABA (free and bound) produced by seawater irrigation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
4
14
0
1
Order By: Relevance
“…However root/shoot, reproductive/vegetative ratios and ABA concentration were found higher under drought stress. Increase in ABA concentration in response to different type of stresses has been previously documented (Aldesuquy & Ibrahim 2001, Gniazdowska et al 2007) while increased ratios under drought stress may be due to enhanced mobilization of assimilates to the roots or reproductive parts. All genotypes showed very strong relationship of ABA with root/shoot (R 00.75; p 50.001) and reproductive/vegetative ratios (R 0 0.85, p 50.001) at each development phase under drought regime.…”
Section: Discussionmentioning
confidence: 70%
“…However root/shoot, reproductive/vegetative ratios and ABA concentration were found higher under drought stress. Increase in ABA concentration in response to different type of stresses has been previously documented (Aldesuquy & Ibrahim 2001, Gniazdowska et al 2007) while increased ratios under drought stress may be due to enhanced mobilization of assimilates to the roots or reproductive parts. All genotypes showed very strong relationship of ABA with root/shoot (R 00.75; p 50.001) and reproductive/vegetative ratios (R 0 0.85, p 50.001) at each development phase under drought regime.…”
Section: Discussionmentioning
confidence: 70%
“…However ABA is only one component of composite hormonal control (Ross & O'Neill, 2001;Nemhauser et al, 2006). It was found that the concentration of ABA and cytokinins increase with increasing in salt concentration (Aldeuquy & Ibrahim, 2001, Vaidyanathan et al, 1999. Abscisic acid may modify the expression of genes affected by salts, and these genes likely play a significant role in the mechanisms of tobacco tolerance to excess salts (Boussiba & Richmond, 1976).…”
Section: Effect Of Excess Salinity On Amino Acid Composition Hormonamentioning
confidence: 99%
“…Salinity exerts negative influences on wheat with an ultimate reduction in yield (Aldesuquy and Ibrahim, 2002;Ghane et al, 2011). In addition to yield reduction, Zaire and Khuble (1990) reported significant interactions between salinity and wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%